THE ROLE OF ICRC (INTERNATIONAL COMMITTEE OF THE RED CROSS) AS A PROTECTOR OF CHILDREN & WOMEN IN THE TIGRAY ETHNIC CONFLICT IN ETHIOPIA IN 2020- 2022 - Nur'ain, Faizah; Amalia, Novi Rizka (UNIDA GONTOR, 2024)
The Tigray non-international armed conflict began in 2020 between Ethiopian military forces including ENDF (Ethiopian National Defense Force), EDF (Eritrean Defense Force), ASF (Amhara Special Forces) and Amhara Militia Groups and TPLF rebels, the conflict began when TPLF rebels attacked Ethiopian military bases operating in the Tigray region and this conflict ended in 2022 in this conflict there have been violations of International Humanitarian Law. The Tigray armed conflict that involved civilians as the main target for women and children. This research aims to analyze the role of the ICRC (International Committee of the Red Cross) based on international humanitarian law as a protector of children & women in the Tigray ethnic conflict in Ethiopia in 2020-2022. This research uses a literature study research design with descriptive qualitative methods, data collection techniques using literature studies looking for sources from several journals, books, previous research and international websites. This research was analyzed using the concept of human rights in war and international organizations. The results of the research show that the ICRC is one of the international organizations that is able to play a role in accordance with the functions of international organizations as an initiator, facilitator and mediator which can ease the burden on the victims when the war lasts until after the war.